2022
DOI: 10.5753/jisa.2022.2371
|View full text |Cite
|
Sign up to set email alerts
|

Design, Implementation and Evaluation of Core/Periphery-based Network-oriented Mixed Reality Services

Abstract: Many new network-oriented services have been developed in recent years, and Multi-access Edge Computing (MEC) has been standardized to improve the responsiveness of services. When deploying services in a MEC environment, it is necessary to consider a service structure that can flexibly switch service behaviors to meet various user requests and that can change service behaviors according to the real-world environment at a low implementation cost. In this paper, we introduce a core/periphery structure for servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Our previous works [12][13][14] have shown that network-oriented services designed based on a core/periphery structure can adapt to environmental changes with low development cost by reusing the core and recreating only the periphery. We numerically investigated the advantages of the core/periphery structure for accommodating information services, represented by chains of functions 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous works [12][13][14] have shown that network-oriented services designed based on a core/periphery structure can adapt to environmental changes with low development cost by reusing the core and recreating only the periphery. We numerically investigated the advantages of the core/periphery structure for accommodating information services, represented by chains of functions 12 .…”
Section: Introductionmentioning
confidence: 99%
“…We numerically investigated the advantages of the core/periphery structure for accommodating information services, represented by chains of functions 12 . In addition, we focused on a shopping experience service using mixed reality (MR) and robots as a use case for realizing a service scenario based on 12 , and we implemented the service with an actual device and demonstrated that service design using a core/periphery structure is effective for robot operation when the numbers of types of devices on the user side and remote side increase 13,15 .…”
Section: Introductionmentioning
confidence: 99%
“…We numerically investigated the advantages of the core/periphery structure for accommodating information services, represented by chains of functions 11 . In addition, we focused on a shopping experience service using mixed reality and robots as a use case for realizing a service scenario based on 11 , and we implemented the service with an actual device and demonstrated that service design using a core/periphery structure is effective for robot operation when the number of device types on the user side and remote side increases 12 , 14 .…”
Section: Introductionmentioning
confidence: 99%